2011
DOI: 10.1890/10-1325.1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling plant ranges over 75 years of climate change in California, USA: temporal transferability and species traits

Abstract: Species distribution model (SDM) projections under future climate scenarios are increasingly being used to inform resource management and conservation strategies. A critical assumption for projecting climate change responses is that SDMs are transferable through time, an assumption that is largely untested because investigators often lack temporally independent data for assessing transferability. Further, understanding how the ecology of species influences temporal transferability is critical yet almost wholly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
205
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 181 publications
(216 citation statements)
references
References 96 publications
(122 reference statements)
10
205
1
Order By: Relevance
“…The predictions for future conditions by the 3-variable standard SDMs were radically different from the 18-variable models. Methods to decide which and how many variables to use for predicting climate change effects are not well established, as such methods tend to rely on cross-validation of known observations for current conditions, which does not establish a model's ability to predict across time (Dobrowski et al 2011), but methods that seek to reduce the number of variables used (e.g., Warren and Seifert 2011) seem promising.…”
Section: Discussionmentioning
confidence: 99%
“…The predictions for future conditions by the 3-variable standard SDMs were radically different from the 18-variable models. Methods to decide which and how many variables to use for predicting climate change effects are not well established, as such methods tend to rely on cross-validation of known observations for current conditions, which does not establish a model's ability to predict across time (Dobrowski et al 2011), but methods that seek to reduce the number of variables used (e.g., Warren and Seifert 2011) seem promising.…”
Section: Discussionmentioning
confidence: 99%
“…At best, the model predictions should be evaluated against an independent data set. However, assessing predictive ability of a model for future conditions is not possible, but transferring models from historical conditions to current conditions and vice versa could be a solution (Dobrowski et al, 2011). However, in many cases, which apply also to the bumblebee data, historical data often suffer from lower sampling intensities, at least in some regions.…”
Section: Modelling Techniquesmentioning
confidence: 99%
“…Increasingly, space-for-time substitution is being applied in biodiversity modeling to project climate-driven changes in species distributions, species richness, and compositional turnover (7)(8)(9)(10)(11). Examination of transferability of models for individual species has exposed concerns regarding the projection of these spatial models across time (12)(13)(14)(15), and it has been suggested that models based on collective biodiversity properties might be more robust (9,16,17). However, the fundamental assumption that spatial relationships between climate and biodiversity can be used to project temporal trajectories of biodiversity under changing climates remains largely untested (but see refs.…”
mentioning
confidence: 99%